PENGENALAN STABILISASI DAN PEMADATAN TANAH DI DESA PASIR LOR KECAMATAN KARANGLEWAS KABUPATEN BANYUMAS (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Development programs in all fields, which are being intensively carried out in Banyumas Regency, include the construction of transportation, buildings, bridges and so on. In the transportation sector, namely the construction of roads at several points in the Banyumas area. Pasir Lor Village is one of the villages in the Karanglewas, Banyumas. Regarding road construction, especially in this area, the author would like to explain about soil material as a support for road construction, namely "Introduction to Soil Stabilization and Compaction".This material aims to provide knowledge for village officials and the community in general. Soil stabilization is an effort to improve soil properties that meet the technical requirements for building construction sites, namely changing the soil properties from existing and poor materials to materials that have better properties. Meanwhile, soil compaction is a process of providing dynamic mechanical energy repeatedly, so that the density of the soil increases due to the reduction of air in the soil, thus the construction will not be easily moved even if it is exposed to large amounts of water.